7-9=-15+-9q

Simple and best practice solution for 7-9=-15+-9q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-9=-15+-9q equation:


Simplifying
7 + -9 = -15 + -9q

Combine like terms: 7 + -9 = -2
-2 = -15 + -9q

Solving
-2 = -15 + -9q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '9q' to each side of the equation.
-2 + 9q = -15 + -9q + 9q

Combine like terms: -9q + 9q = 0
-2 + 9q = -15 + 0
-2 + 9q = -15

Add '2' to each side of the equation.
-2 + 2 + 9q = -15 + 2

Combine like terms: -2 + 2 = 0
0 + 9q = -15 + 2
9q = -15 + 2

Combine like terms: -15 + 2 = -13
9q = -13

Divide each side by '9'.
q = -1.444444444

Simplifying
q = -1.444444444

See similar equations:

| 2x^2-11x=1 | | 25y^2-15y=5y | | 6x+6=126+6x | | 12(3x-1)=3(12x+2) | | 177-6x=39x+17 | | 12y^2-27=0 | | 8+5r-7=9r+9-6r | | 8x-35=25-2x | | 8-8x=133-43x | | 3x+17=13x-83 | | 7(t^2+5t-9)+t=t(7t-2)+13 | | 4t=-44 | | -7x+6=90 | | 3x+17=7x+3 | | 9x+5x-2x=0 | | 4=0.5(3x-4) | | 10x-15=-5x+30 | | 5s+11s=80 | | 115-5x=5x+15 | | 8+5y=-27 | | 3x^2-13x-16=-6 | | 0.05(x+30)-0.02(x-10)=3.2 | | -4586+y=5876 | | -9(3b+1)+(28b-2)=0 | | 5x+9(x-17)=8(9+x)+6x | | 9(2.5)-10= | | 3(2.5)+5= | | 83-4x=23x+20 | | 7-7x=82-42x | | =20+3 | | h-6j+7h+10j= | | 3.2q-3.6-4.1q=1.9q-4.8 |

Equations solver categories